Adapting to Détente: US Policy on Korean Unification in 1968-1973 - D. A. Sadakov (Vestnik MGIMO-Universiteta)
The article studies the history of the US foreign policy adaptation to détente that started in the late 1960s. By this time the Americans had strong military and political positions on the Korean peninsula. Washington managed to thwart DPRK attempts in 1966–1969 to destabilize the situation in the South. Americans saw growing inter-Korean contacts as a new challenge. With détente gaining momentum, this led to the obsolescence of some American foreign policy instruments in the region, including the US-controlled UN Commission on the Unification and Rebuilding of Korea. Another challenge for the Americans was the North Koreans' «diplomatic offensive,» which strengthened North Korea's position in the world. It tried to use the accumulated political weight to turn the annual debate on the Korean issue in the UN General Assembly from a formality to something real. At the same time, the military threat posed by the Democratic People's Republic of Korea, for example, in the 1973–1975 conflict along the Northern Boundary Line, remained relevant.Nevertheless, in 1968–1973 the Americans succeeded in reshaping their policy toward Korea under conditions of a dramatic improvement in the international situation of the DPRK and settlement of US-Chinese relations. The Americans managed to eliminate the obsolete UN Commission on the Unification and Restoration of Korea with minimal losses. They ensured that the discussion of the Korean question in the United Nations would not have a destructive influence on the internal political life of the South. Under these conditions, the inter-Korean dialogue remained merely a political game of the regimes on the peninsula. Preserving the status quo in the region was the main result of US diplomacy’s manipulative techniques. Such approaches are still relevant for the modern US foreign policy – getting rid of international instruments, which have exhausted their purpose.